KAJIAN PUSAT SPIRITUAL DALAM KONTEKS JAWA - Karen Claudia; Rudy Trisno (Jurusan Arsitektur dan Perencanaan, 2019)
Spiritual adherents now long for a community. In response to that, a design for a spiritual center is proposed to accommodate the spiritual needs of a spiritual community in Jakarta. Designing a spiritual center requires an element of the transcendent to be infused into the building. Modern composition and technology is used as a language to translate the typology appropriate to the context into an actual building. An insight on traditional Javanese architecture shows that harmony between mass and void, nature and man, light and shadow, and space and time is needed to synthesize spirituality in architecture. Therefore, the conclusion and finding is that unity between dualities is important in designing spiritual architecture. AbstrakPenganut spiritualitas memerlukan sebuah komunitas, oleh sebab itu, diajukan perancangan pusat spiritual untuk mewadahi kebutuhan spiritual bagi komunitas spiritual di Jakarta. Dalam perancangan pusat spiritualitas diperlukan elemen transenden dalam bangunan, maka digali tipologi sesuai konteks yang diterjemahkan ke dalam bangunan melalui komposisi dan teknik modern. Metode penilitian yang diperlukan untuk menimbulkan suasana spiritual adalah keseimbangan antara mass dan void, alam dan manusia, cahaya dan bayangan, serta ruang dan waktu. Sehingga dapat disimpulkan dan ditemukan bahwa kesatuan dalam dualitas adalah prinsip penting dalam proses perancangan arsitektur spiritual.